2015
DOI: 10.1890/14-0772.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in beta diversity between exotic and native grasslands vary with scale along a latitudinal gradient

Abstract: Biodiversity can be partitioned into alpha, beta, and gamma components, and beta diversity is not as clearly understood. Biotic homogenization predicts that exotic species should lower beta diversity at global and continental scales, but it is still unclear how exotic species impact beta diversity at smaller scales. Exotic species could theoretically increase or decrease beta diversity relative to natives depending on many factors, including abiotic conditions, community assembly history, management, dispersal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 55 publications
7
26
0
Order By: Relevance
“…Similar to our results, in India, the United States and Chile, grassland homogenization has been driven by the spread of widespread non‐native species in response to habitat fragmentation and human settlement (MacDougall et al. ; Dar & Reshi ; Martin & Wilsey ; Fisher et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, in India, the United States and Chile, grassland homogenization has been driven by the spread of widespread non‐native species in response to habitat fragmentation and human settlement (MacDougall et al. ; Dar & Reshi ; Martin & Wilsey ; Fisher et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…That taxonomic homogenization of grassland communities at the focal spatial scale, i.e. within a locality, may occur as a result of exotic species proliferation is also supported by studies examining exoticdominated prairie grasslands, which-when compared to native grasslands-reveal lower beta-diversity locally (Martin & Wilsey, 2015).…”
Section: Beta-diversitymentioning
confidence: 83%
“…Some studies have found that a high Gram negative : positive ratio is indicative of a higher environment stress (Clark et al 2009, Feng andSimpson 2009), and this is consistent with our finding that the Gram negative : positive ratio increased with increasing latitude, and high-latitude sites had lower temperatures and less precipitation. Exotic species may homogenize biota, or lower beta diversity, at a variety of spatial scales Reshi 2015, Martin andWilsey 2015). In native communities, composition of soil communities at continental and global scales should reflect geographic variation in abiotic condition, soil types, and other dominant species that influence the soil community, resulting in high beta diversity at geographic scales (Wu et al 2016, Price et al 2018, Ren et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive species, particularly plants, can cause changes in species richness, edaphic factors, hydrological factors, and nutrient cycling in the invaded ranges (Vil a et al 2011, Hughes et al 2016. Through these changes, they can cause biotic homogenization, in which beta diversity decreases and local plant and animal communities become increasingly similar (McKinney and La Sorte 2007, Lambdon et al 2008, Martin and Wilsey 2015.…”
Section: Introductionmentioning
confidence: 99%